(untitled) (ENTHYMEMA, 2020)
Between the end of dictatorship (1974) and the entry into the EEC (1986), Portugal starts a process of rethinking of its own past which, from a literary point of view, corresponds to a renewed attention to the author-narrator-character relationship. Among the examples of metanarrative characters not yet considered by critics, the intervention will focus on O que diz Molero by Dinis Machado (1977) and Walt, or frio and o quente by Fernando Assis Pacheco (1978).